Glycolate and Glyoxylate Metabolism by Isolated Peroxisomes or Chloroplasts - Kisaki, T. (1969)
Chloroplasts, mitochondria, and peroxisomes from leaves were separated by isopycnic sucrose density gradient centrifugation. The peroxisomes converted glycolate-(14)C or glyoxylate-(14)C to glycine, and contained a glutamate: glyoxylate aminotransferase as indicated by an investigation of substrate specificity. The pH optimum for the aminotransferase was between 7.0 and 7.5, and the Km for l-glutamate was 3.6 mm and for glyoxylate, 4.4 mm. The reaction of glutamate plus glyoxylate was not reversible. The isolated peroxisomes did not convert glycine to glyoxylate nor glycine to serine. Peroxisomes did not oxidize glycolate or glyoxylate to CO(2). Chloroplasts could very slowly oxidize glyoxylate, but not glycolate, to CO(2). Chloroplast oxidation of glyoxylate was heat labile and widely distributed among plants. Oxidation was stimulated by light and oxygen. but was not inhibited by 3-(3,4-dichlorophenyl)-1,1-dimethylurea (DCMU). A scheme for the distribution of enzymes associated with glycolate metabolism and photorespiration is presented. Glycolate biosynthesis occurs in the chloroplasts. In the peroxisomes, glycolate is oxidized with O(2) uptake to glyoxylate by glycolate oxidase, and the glyoxylate is converted to glycine by glutamate:glyoxylate aminotransferase. Further metabolism of glycine does not occur in the peroxisomes. It is possible that excess glyoxylate from the peroxisomes could return to the chloroplasts to be reduced to glycolate or oxidized to account for part of the CO(2) loss during photorespiration.